The digitalisation of service work – social partner responses in Denmark, Sweden and Germany. (August 2017) - Ilsøe, Anna
The discussion on the digitalisation of work has intensified in recent years. The literature points to two main trends accelerated by digitalisation – work automation that eliminates or changes job functions, and the creation of work without jobs via digital platforms. This article addresses the question as to how social partners define digitalisation of work and their perception of its consequences, while also looking at their recent responses to it. Drawing on interviews with unions and employers' organisations in Denmark, Sweden and Germany, it examines social partner initiatives in the unilateral, tripartite and bipartite arenas on various forms of neo-corporatist labour market regulation. The focus is on service work in the private sector, an area of the economy currently under pressure from both automation and the trend towards work without jobs. Whereas the social partners seem to be very active in the unilateral arena in all three countries, responses differ in the tripartite and bipartite arenas. The article concludes by discussing the strengths and weaknesses of the responses in the face of current digitalisation trends and existing models of labour market regulation.